Maqasid al-Shariah dan Konvergensi ESG di Pasar Modal Islam: Tinjauan Sistematis tentang Kerangka Kerja, Bukti Empiris, dan Tantangan Implementasi - Didik Gunawan (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This study aims to synthesize the literature on the convergence between Maqasid al-Shariah and Environmental, Social, and Governance (ESG) principles in the Islamic capital market ecosystem. Using a Systematic Literature Review (SLR) of selected literature from 2020 to 2025, this study evaluates various theoretical frameworks, empirical evidence, and implementation challenges faced by Islamic financial instruments such as green sukuk. The research findings indicate that Maqasid al-Shariah provides a substantial ethical foundation for ESG metrics, which in turn enhances market resilience and company value amidst global economic uncertainty. However, the study also identifies significant barriers in the form of regulatory fragmentation and the risk of greenwashing, which could threaten market integrity. The primary value of this research lies in providing a strategic roadmap for regulators and practitioners to harmonize global Sharia sustainability standards. By bridging the gap between formal Sharia compliance and measurable environmental impact, this study makes a crucial contribution to the development of a more transparent and public-benefit-oriented Islamic financial system in the future.